MANAJEMEN PEMBIAYAAN PENDIDIKAN MELALUI DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMPN 52 BANDUNG - Okke Rosmala Dewi; Kiki Yuantika; Romlah Rosmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The School Operational Assistance Fund (Bantuan Operasional Sekolah/BOS) is one of the Indonesian government's programs aimed at improving access, equity, and the quality of education by providing financial support for non-personnel operational expenses in educational institutions. This study aims to analyze the management of educational financing through the BOS Fund in improving the quality of education at SMPN 52 Bandung. The study employed a qualitative approach using a descriptive research method. Data were collected through observation, interviews, and documentation. The findings indicate that the management of the BOS Fund at SMPN 52 Bandung has been implemented through the functions of planning, organizing, implementation, and supervision in accordance with the government's technical guidelines. The planning process was carried out through the preparation of the School Activity and Budget Plan (Rencana Kegiatan dan Anggaran Sekolah—RKAS), involving various stakeholders. Budget implementation was conducted in a transparent and accountable manner. Supervision was carried out by the school principal, the school committee, the local education office, and the government through the BOS reporting system. The management of the BOS Fund has contributed to improving the quality of education by providing educational facilities and infrastructure, enhancing teachers' competencies, procuring learning media, and improving student services. However, the school still faces challenges, including limited funding compared to its operational needs and frequent changes in government regulations.